1997
DOI: 10.1111/j.1600-0781.1997.tb00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical or oral administration with an extract of Polypodium leucotomos prevents acute sunburn and psoralen‐induced phototoxic reactions as well as depletion of Langerhans cells in human skin

Abstract: Sunburn, immune suppression, photoaging, and skin cancers result from uncontrolled overexposure of human skin to solar ultraviolet radiation (UVR). Preventive measures, including photoprotection, are helpful and can be achieved by topical sunscreening agents. Polypodium leucotomos (PL) has been used for the treatment of inflammatory diseases and has shown some in vitro and in vivo inmunomodulating properties. Its beneficial photoprotective effects in the treatment of vitiligo and its antioxidant properties enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 36 publications
0
85
0
2
Order By: Relevance
“…34 PL has also been shown to reduce phototoxicity by decreasing inflammation (acute sunburn and depletion of Langerhans cells) and photoaging in both humans and an animal model. 35,36 In addition, PL has been reported to prevent the loss of cell viability (apoptosis) and proliferation induced by UVA. 37 Moreover, PL has also been proven to reduce inflammation through down-regulation of tumor necrosis factor-␣.…”
Section: Discussionmentioning
confidence: 99%
“…34 PL has also been shown to reduce phototoxicity by decreasing inflammation (acute sunburn and depletion of Langerhans cells) and photoaging in both humans and an animal model. 35,36 In addition, PL has been reported to prevent the loss of cell viability (apoptosis) and proliferation induced by UVA. 37 Moreover, PL has also been proven to reduce inflammation through down-regulation of tumor necrosis factor-␣.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The possibility that reactive oxygen species-associated effects are responsible for PUVA-induced effects such as immune suppression is supported by the observation that the antioxidative polypodium leucotomos extract has been shown to inhibit PAF production 23 and several types of UV and/or PUVA-induced immunological alterations, such as depletion of antigenpresenting Langerhans cells in human skin. 24 Moreover, the isoflavone genistein, a specific inhibitor of tyrosine kinase, has been shown to inhibit chemical carcinogeninduced reactive oxygen species and PUVA-induced photodamage, including inflammatory skin changes such as dermal neutrophilic and lymphocytic infiltration. 25 We observed that ex vivo PUVA-treated and UVAtreated PC but not unirradiated PC induced immune suppression in a dose-dependent manner (Figure 1c).…”
Section: Discussionmentioning
confidence: 99%
“…Two to three mice per treatment group were sacrificed before and at various time points (24,48,72,120, and 360 hours) after PUVA exposure. Approximately 1 cm 2 of dorsal skin was excised per mouse, fixed immediately in 4% buffered formaldehyde, processed routinely, and sectioned at 5 m for hematoxylin and eosin (H&E) staining.…”
Section: Histological Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…It also possesses regenerative skin properties, and prevents UVBinduced photo-aging [19,20]. * Fernblock, an extract obtained from the fern Polypodium leucotomos, inhibits UVB and PUVA therapy-induced erythema in vivo [21]. It is a potent antioxidant and has shown immunemodulating capability and inhibition of pro-inflammatory cytokines, such as TNF-α or IL-6 [22].…”
Section: Antioxidantsmentioning
confidence: 99%